Catalytic effects of calcium and potassium on a curved char surface in fuel reburning: A first-principles study on the adsorption of nitric oxide on single-wall carbon nanotubes with metal decoration. (15th April 2017) - Liu, Lei; Jin, Jing; Hou, Fengxiao; Li, Shengjuan; Lee, Chang-Ha
Abstract: To investigate the role of a curved char surface in the nitric oxide (NO)-char reaction, single-wall carbon nanotubes (SWCNTs) were proposed as a model for simulating the curved char surface in first-principles calculations. The effect of calcium and potassium decoration on the adsorption of NO was compared for SWCNTs and graphene, the latter of which represented a flat char surface. The contribution of a curved surface to the NO-char reaction was insignificant in the absence of metals, as the binding energy of NO on pure SWCNTs was only 13% of that on pure graphene. In contrast, when calcium or potassium was present, NO adsorption on the curved surface became significant as the binding energies of NO on calcium- or potassium-decorated SWCNTs increased to 72% and 18% of those on the corresponding decorated graphene surfaces, respectively. The catalytic effect of calcium and potassium was attributed to electron transfer and backdonation between the 4s- and 3d-orbitals of the metal atoms and the NO molecule. Thus, the studies into NO adsorption on flat and curved char surfaces render it possible to determine the degree of catalytic effect of these two metals on the char surface during fuel reburning. Graphical abstract: Highlights: SWCNTs were proposed to simulate the curved char surface in the fuel reburning. The catalytic effects of Ca and K were studied by Ca- or K-decorated SWCNTs. Without Ca or K, the binding energy of NO on curved char surface was trivial. When Ca or K was present, NO adsorption on the curved surface became significant. Electrons of Ca and K in 4s- and 3d-orbitals transferred to the NO molecule.